2018
DOI: 10.1136/heartasia-2018-011047
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to treatment among patients with newly diagnosed hypertension in Nepal

Abstract: A number of factors emerged as barriers and facilitators to hypertension treatment. This information can be useful in designing appropriate health interventions to improve hypertension management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(69 citation statements)
references
References 26 publications
5
64
0
Order By: Relevance
“…No additional eligible studies were found in Nepalese journals and on websites of the Nepali Government, professional and regulatory organisation, and national and international agencies. Finally, we included 14 studies [43][44][45][46][47][48][49][50][51][52][53][54][55][56] for qualitative synthesis (see Fig 2). None of the studies were included in the quantitative synthesis of effect sizes because of the signi cant differences in their aims, methods, interventions/exposures and outcome measures.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…No additional eligible studies were found in Nepalese journals and on websites of the Nepali Government, professional and regulatory organisation, and national and international agencies. Finally, we included 14 studies [43][44][45][46][47][48][49][50][51][52][53][54][55][56] for qualitative synthesis (see Fig 2). None of the studies were included in the quantitative synthesis of effect sizes because of the signi cant differences in their aims, methods, interventions/exposures and outcome measures.…”
Section: Study Selectionmentioning
confidence: 99%
“…Only a study conducted in Acham (hospital and community-based) included participants from a rural area [47]. Half of the studies were completed in 2015 or later; and more than half of the studies assessed the barriers and enablers of hypertension treatment and control [51][52][53][54][55][56]. They applied qualitative methods (n=3) [52][53][54], quantitative methods (n=4) [51,56] and mixed methods (n=1) [55].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations